Implementasi Pendekatan Saintifik (K13) pada Pembelajaran Fikih di Yayasan Perguruan Islam Azizi - Apriza, Dipa; Sitorus, Khairun Nisa; Ardana, Rafli; Arlina, Arlina (Lembaga Yasin AlSys, 2025)
This study aims to describe the implementation of the scientific approach (K13) in fiqh learning at Yayasan Perguruan Islam Azizi. The research used a qualitative method with field research and data collection techniques through observation, interviews, and documentation. Data analysis techniques included data reduction, data presentation, and verification or conclusion drawing. The data validity technique adopted the interactive model (Miles and Huberman). The results indicate that Yayasan Perguruan Islam Azizi still uses the 2013 curriculum (K13). Based on observations and interviews, the fiqh teachers at Yayasan Perguruan Islam Azizi have implemented the scientific approach in the learning process. This approach involves applying scientific steps such as observing, questioning, gathering information, reasoning, and communicating. It is expected to enhance students' understanding and skills in fiqh material and build critical and analytical thinking abilities. Thus, the implementation of the scientific approach in fiqh learning holds significant potential for continuous application to improve the quality of Islamic education.